Karakteristik dan Model Pendidikan Islam bagi Anak Berkebutuhan Khusus (ABK) Tuna Grahita - Tsabitah (Anakta : Jurnal Pendidikan Islam Anak Usia Dini, 2025)
This study aims to explore the characteristics of children with intellectual disabilities (ABK tuna grahita) and to understand the Islamic education model implemented in the context of a special needs school. The research employs a descriptive qualitative approach with data collected through in-depth interviews with Ms. Shofia, the Vice Principal of SLB Nur Rahmah. The findings indicate that children with intellectual disabilities experience limitations in cognitive and adaptive aspects, which affect their learning process and social interactions. The Islamic education model applied includes individualized approaches, reinforcement of spiritual values, and active involvement of families. Despite various challenges, such as social stigma and limited facilities, a contextual approach grounded in Islamic values has proven effective in supporting the holistic development of these children.